Auditory verbal hallucinations in first-episode psychosis: a phenomenological investigation. Issue 1 (January 2016) - Upthegrove, Rachel; Ives, Jonathan; Broome, Matthew R.; Caldwell, Kimberly; Wood, Stephen J.; Oyebode, Femi
Abstract : Background: In dimensional understanding of psychosis, auditory verbal hallucinations (AVH) are unitary phenomena present on a continuum from non-clinical voice hearing to severe mental illness. There is mixed evidence for this approach and a relative absence of research into subjective experience of AVH in early psychosis. Aims: To conduct primary research into the nature of subjective experience of AVH in first-episode psychosis. Method: A phenomenological study using diary and photo-elicitation qualitative techniques investigating the subjective experience of AVH in 25 young people with first-episode psychosis. Results: AVH are characterised by: (a) entity, as though from a living being with complex social interchange; and (b) control, exerting authority with ability to influence. AVH are also received with passivity, often accompanied by sensation in other modalities. Conclusions: A modern detailed phenomenological investigation, without presupposition, gives results that echo known descriptive psychopathology. However, novel findings also emerge that may be features of AVH in psychosis not currently captured with standardised measures.